Insight into the critical morphological characteristics of earthquake-induced sequential rock avalanches in weathered-fractured rock cliffs - Guo, Shuangfeng; Liu, Yajing; Zhang, Peng; Zhu, Rui; Qian, Youkai (Frontiers in Earth Science, 2023)
Rock avalanches are a significant threat to transportation or hydraulic infrastructure, as they can also cause catastrophic secondary destruction in large practical engineering or to nearby residents. Earthquake-induced rock avalanches have been the most common and prominent natural hazard phenomena among geological hazards in recent years. Earthquake-induced rock avalanche events usually begin when a massive rock mass or multiple rock masses separate from a rock slope, progressively fragmenting and transforming into fast-moving, cohesionless rock falls. Earthquake-induced sequential collapse often occurs on weathered and fractured rock cliffs in horizontal strata, and its kinematic dynamics and destabilization mechanism are significantly different from those of isolated collapse due to weathering. In this study, the failure characteristics of the initiation and movement process of the avalanche are revealed in detail, through physical model experiments and analytical solutions, thereby obtaining an earthquake-controlled mechanical model equation. Our methods use the inflection points of the displacement time curve at the top of the rock wall and the digital images acquired by the shaking test bench to quantify the critical damage time point and to characterize the critical morphology of continuous collapse. A mathematical model of analytical solution is proposed, which aims to address the kinematic mechanics mechanism of sequential collapse under translational and rotational motion models. The comparative analysis results of the experiment and analytical solutions reveal that the transformed motion pattern is controlled by the ratio between the model stacking height, the rock block size, and the seismic acceleration. Whereas the rotational motion pattern is mainly influenced by the nodal dip angle, model stacking height, and seismic acceleration. The results of the study are of great scientific importance to elucidate the destruction mechanism of the earthquake-induced sequential collapse of rock avalanches and to determine the evolution characteristic of subsequent rockfalls motion of dangerous rocks. The proposed framework for the analysis of rock avalanches can be applied to understand the critical topographic features and mechanical mechanism behavior of analogous geological hazards.